Role of small addition of liquefied petroleum gas (LPG) on laminar burning velocity of hydrous ethanol - Kustanto, Muh Nurkoyim; Sasongko, Mega Nur; Wardana, I Nyoman Gede; Yuliati, Lilis (Eastern-European Journal of Enterprise Technologies, 2019)
Ethanol is an appropriate substitution for gasoline fuel in spark ignition engines. Ethanol has a high-octane number allowing to use it in the higher compression ratio of the engine. A better understanding of combustion characteristics of ethanol is needed before it is used widely in the spark ignition engine. One of the most important parameters of the replacement fuel is the burning velocity. Therefore, the purpose of the research is to investigate experimentally the effect of the small addition of liquefied petroleum gas (LPG) on the laminar burning velocity of hydrous ethanol. The combustion characteristic of the ethanol and LPG mixture was examined in a cylindrical combustion chamber with a diameter of 10.8 cm and a length of 17 cm. The flame had a spherically expanding shape. Fuel mixture was ignited by sparks inside the cylinder and the flame diameter was measured from the flame image captured by the high-speed camera. The research used two types of ethanol fuel such as anhydrous ethanol and hydrous ethanol containing 0.3 % of water. The percentage of LPG in the fuel mixture was varied from 0 % to 20 %. The results showed that the addition of 10 % LPG in ethanol increases laminar burning velocity. For anhydrous fuels, ethanol burning velocity is higher than for LPG and the highest burning velocity is in ethanol, to which 10 % LPG is added while the lowest is in LPG. Besides, the effect of water content in ethanol fuel causes a decrease in combustion speed significantly. But the addition of LPG up to 10 % makes hydrous ethanol relatively more robust to rising water content due to the combustion reaction is helped by a higher radical concentration in LPG. This is caused by two factors: the partial preheating zone resulted by the hydroxyl group (OH) of ethanol that supplied more heat energy and the high concentration of radicals in LPG that assists the combustion reaction.